Faktor-Faktor yang Berhubungan dengan Terjadinya Resiko Bunuh Diri pada Remaja di SMA Muhammadiyah Batudaa Kabupaten Gorontalo - Marlanda Djafar; Rona Febriyona; Rini Asnawati (Pusat Riset dan Inovasi Nasional, 2026)
The recent increase in suicide cases, particularly among adolescents, is due to a lack of awareness among adolescents regarding several risk factors for suicide, including psychological, family, and social factors. The purpose of this study was to determine the factors associated with the risk of suicide in adolescents. This research method used a quantitative correlational approach. The population in this study was 176 students at Muhammadiyah Batudaa High School, Gorontalo Regency, and a sample size of 64. The analyses used were univariate and bivariate analysis. The results of the study indicate that psychological factors, family factors, and environmental factors each have a chi-square value > chi-square p = 0.000. The third factor has a value <0.05, thus Ha is accepted. Therefore, it can be concluded that there is a relationship between psychological factors, family factors, and environmental factors with the risk of suicide among students at Muhammadiyah Batudaa High School, Gorontalo Regency.